Fewer Jobs or Smaller Paychecks? Aggregate Crisis Impacts in Selected Middle-Income Countries - Khanna, Gaurav; Newhouse, David; Paci, Pierella (2012)
This paper reviews evidence from 44 middle-income countries on how the recent financial crisis affected jobs and workers' incomes. In addition to providing a rare assessment of the magnitude of the impact across several middle-income countries, the paper describes how labor markets adjusted and how the adjustments varied for different types of countries. The main finding is that the crisis affected the quality of employment more than the number of jobs. Overall, the slow-down in earning growth was considerably higher than that in employment, and the decline in gross domestic product was associated with a sharp decline in output per worker, particularly in the industrial sector. In several counties, hours per worker declined and hourly wages changed little. But both the magnitude and nature of the adjustments varied considerably across countries. For a given drop in gross domestic product, earnings declined more in countries with larger manufacturing sectors, smaller export sectors, and more stringent labor market regulations. In addition, overall employment became more sensitive to growth in gross domestic product. These findings have implications that go beyond the recent financial crisis as they highlight (i) the limitations of focusing policy responses on maintaining jobs and providing alterative employment or replacement income for the unemployed, and (ii) the critical role of fast-track data systems that are capable of monitoring ongoing labor market adjustment during economic downturns, in supporting the design of effective policy responses.